Prognostic impact of glioblastoma stem cell markers OLIG2 and CCND2. (30th September 2019) - Bouchart, Christelle; Trépant, Anne‐Laure; Hein, Matthieu; Van Gestel, Dirk; Demetter, Pieter
Abstract: Aims: Glioblastoma (GBM) is the most common and lethal malignant brain tumor in adults. Glioma stem cells (GSCs) are implicated in this poor prognosis and in radio(chemo‐)resistance. We have previously demonstrated that among potentially highly specific GSC markers oligodendrocyte lineage transcription factor 2 (OLIG2) appears to be the most specific and cyclin D2 (CCND2) the only one related to cell cycle regulation. The purpose of this work was to investigate the clinical significance and the evolution of OLIG2 and CCND2 protein expression in GBM. Methods and results: Immunohistochemical expression analysis of Olig2 and Ccnd2 was carried out on a cohort of human paired GBM samples comparing initial resections with local recurrent tumors after radiation therapy (RT) alone or radio‐chemotherapy with temozolomide (RT‐TMZ). Uni‐ and multivariate logistic regression analysis revealed that significant risk factors predicting early mortality (<12 months) are: subtotal surgery for recurrence, time to recurrence <6 months, Ccnd2 nuclear expression at initial surgery ≥30%, and Olig2 nuclear expression <30% at second surgery after RT alone and RT‐TMZ. Conclusions: We demonstrated that patients for whom nuclear expression of Olig2 becomes low (<30%) after adjuvant treatments have a significantly shorter time to recurrence and survival reflecting most probably a proneural to mesenchymal transition of the GSCs population. We also highlighted the fact that at initial surgery, high nuclear expression (≥30%) of CCND2, a G1/S regulator specific of GSCs, has a prognostic value and is associated with early mortality (<12 months). Abstract : We investigated by immunohistochemistry the clinical significance and the evolution of Oligodendrocyte lineage transcription factor 2 (OLIG2) and cyclin D2 (CCND2) protein expression, two markers highly specific of glioma stem cells, on a cohort of human paired glioblastoma samples comparing initial resections with recurrent tumors after radiation therapy alone or radio‐chemotherapy with temozolomide according to the Stupp regimen. Our study highlighted for the first time the prognostic value of high nuclear expression of CCND2 at initial surgery which is associated with early mortality and patients for whom nuclear expression of OLIG2 becomes low after adjuvant treatments have a significantly shorter time to recurrence and survival reflecting most probably a proneural to mesenchymal transition of the stem cells population.